Red Man Syndrome Adverse Reaction following Intravenous Infusion of Cefepime - Panos, George (American Society for Microbiology, 2012)
We report the first case of cefepime-induced “red-man syndrome,” which appeared 30 min following drug infusion and was confirmed with a rechallenge test. This syndrome is classically associated with vancomycin infusion and is the result of non-IgE mediated mast cell degranulation. While this adverse effect can be easily managed with drug withdrawal and antihistamine administration, it is unknown whether it can be prevented with slower cefepime infusion and preinfusion antihistamines, as is the case with vancomycin.